INSTITUTIONAL RESEARCH AGENDA EXECUTION THROUGH UNDERGRADUATE THESIS OUTPUT - Edgar Allan Dela Cruz Mendoza (Journal of Business on Hospitality and Tourism, 2016)
As the universities in the Philippines aspires to be among the leading institutions within ASEAN together with other ASEAN universities, research initiatives have been one of the way for them to internationalize. Research agenda were created to align all the efforts of the higher education institution towards few, if not one, foci. This paper is a formative evaluation of the initial execution of a certain autonomous university in the country. Utilization of the research agenda as well as the research capability of the advisers is looked into in this paper.    The 10-fold agenda, sixty eight (68) theses and thirty (30) faculty members, twenty (20) of which are thesis advisers, are used as data for the document analysis. Slovin’s formula is shown to set the minimum required number of data needed. The census of the population is gathered. Descriptive statistics, such as frequency and percentage, are employed since the research is qualitative in nature.    Among the 68 theses analyzed, 6 are classified as Type A, 18 are Type B, and the rest are Type C. Scoring is based on the panel or paper critique done at the end of the semester. The bias is reduced through a ranking of score, instead of using the weighted mean to eliminate sensitivity to extreme values.            In its entirety, this research is valuable to the institution as its results could be used to improve the current system of the institution and further strengthen its research culture. At the end of this paper, a model is proposed to aid the other institution in formulating its own research agenda through internal and external assessment – Tri-Focal Assessment for Research Agenda Creation (TARAC).